Aphid Viruses: A Brief View of a Long History - Guo, Ya; Ji, Ning; Bai, Lisha; Ma, Juntian; Li, Zhaofei (Frontiers in Insect Science, 2022)
Aphids are common agricultural pests with a wide range of hosts from agriculture to forestry plants. As known, aphids also serve as the major vectors to transmit plant viruses. Although numerous studies have focused on interactions between aphids and plant viruses, little is known about the aphid viruses, i.e., the insect viruses that are infectious to aphids. In the past four decades, several aphid viruses have been identified in diverse aphid species. In this review, we present a brief view of the aphid pathogenic viruses from several aspects, including classification of aphid viruses and characters of the viral genome, integration of viral sequences in host genomes, infection symptoms and influence on aphids, as well as host range and transmission modes. Taken together, these studies have increased our understanding of the rarely known aphid viruses, and will potentially contribute to the development of new strategies for controlling aphid populations.